Mary Antonucci celebrated her 85th birthday (Raton Range Raton, New Mexico, 1992)
Newspaper Article on the 85th birthday of Mary Antonucci.
Master list item #: 27
File location is in the Raton File Cabinet
Keywords: Antonucci, Mary; Kern, Louise; Antonucci, Mark; Antonucci, Onorio Jr; Gigante, Rose; Rea, Marina; Rea, Domenic; Marchet, John; Marchet, Marilyn; Marchet, Dennis; Grubelnik, Mary Lou; Grubelnik, John; Vanetta, Lisa; Marchet, Jon; Marchet, Susan; Marchet, Jared; Iafrate, Albert; Iafrate, Betty; Antonucci, Frank; Antonucci, Betty; Antonucci, Alan; Williams, Katina; Chicarelli, Jim; Chicarelli, Jam; Chicarelli, Mark; Chicarelli, Michael; Chicarelli, Cheri; Chicarelli, Julie; Krulyac, Maureen; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; San Jose, California; Colorado Springs, Colorado; Denver, Colorado; Maxwell, New Mexico